Peningkatan Kemampuan Menulis Puisi Dengan Pendekatan Semiotika Berbasis Kearifan Lokal Bagi Siswa Smp N 17 Tanjung Jabung Timur - Mestika Putra, Yoga; Triandana, Anggi; Kartika Putri, Aprilia; Fitriah, Siti; Amri, Ulil; Wulandari, Sovia (Pendidikan Sejarah FKIP Universitas JAMBI, 2026)
: This research is driven by the low poetry writing skills among students at SMP N 17 Tanjung Jabung Timur. The primary challenges identified include difficulties in generating ideas and utilizing meaningful diction. The objective of this study is to describe the improvement in students' poetry writing abilities through the application of a semiotic approach based on local wisdom. The implementation methods consisted of preparation, training, content production practice, as well as monitoring and evaluation. The research subjects involved 7th and 8th-grade students of SMP N 17 Tanjung Jabung Timur. Data collection techniques included poetry writing tests, classroom activity observations, and documentation. Data analysis was conducted using both descriptive qualitative and quantitative methods. The results indicate a significant increase in the average scores of students' poetry writing abilities. Qualitatively, students were able to transform local cultural signs—such as coastal community traditions and the mangrove ecosystem—into profound poetic metaphors through the analysis of icons, indices, and symbols. The study concludes that a semiotic approach based on local wisdom is effective in improving the quality of students' poetry while simultaneously strengthening local cultural literacy.